Visual Allusions to the Mexican-American War: Paintings from the Düsseldorf School - Annus, Irén (Acta Hispanica, 2020)
The Mexican-American War (1846-48) is often described as the first major war in US history inspired by the idea of Manifest Destiny. The significance of this war, however, has not been matched by a rigorous scrutiny of its representation in contemporary visual culture. This study hopes to contribute to filling this void through an iconological investigation of three American paintings made in the Düsseldorf Academy, by now canonized and perceived as ultimate visual treatments of the topic. The paper first discusses the war and the public debates surrounding it in the US, then turns to the visual scene and introduces how the war was portrayed in various art forms. Next, it touches upon the artistic milieu of the Düsseldorf Academy in preparation for the analysis of the three paintings to follow. The study argues that these images depart from the American tradition of depicting war through concrete battle scenes. Instead, they offer symbolic representations or allusions, approaching the war in terms of morality, political philosophy and its potential social and economic consequences, while also employing ambiguity to urge viewers to contemplate on the implications of the war. In the meanwhile, they seem to express little if any consideration for the impact of the war on Mexico, its culture, and people.